Development and characterization of an immortalized nasopharyngeal epithelial cell line to explore airway physiology and pathology in yak (Bos grunniens) - Qi, Jiancheng; Zhang, Jizong; Huang, Fangyuan; Xie, Yue; Guo, Hongrui; Gou, Liping; Zuo, Zhicai; Fang, Jing (Frontiers in Veterinary Science, 2024)
Airway epithelial cells play a crucial role in investigating the physiological and pathological mechanisms of the respiratory tract in yaks, a species whose unique respiratory system has garnered extensive interest. Despite this growing interest, there currently are no available airway epithelial cell lines from yaks, underscoring the crucial need to establish a yak respiratory epithelial cell line. Therefore, our objective was to isolate a population of primary yak nasopharyngeal epithelial cells (pYNE) and transform them into immortalized yak nasopharyngeal epithelial cells (iYNE), assessing their suitability as an in vitro model.Employing a combined method of physical elimination and differential adhesion, we successfully isolated a population of high-purity pYNE, and developed an iYNE line through pCI-neo-hTERT plasmid transfection. Karyotype and transmission electron microscopy analyses confirmed that pYNE and iYNE share identical morphologies and structures. Gel electrophoresis and real-time PCR analyses demonstrated that pYNE and iYNE expressed similar levels of KRT18 and CDH1 genes (p ≥ 0.541). Notably, iYNE expressed a significantly high level of TERT gene expression (p < 0.001). Immunofluorescence analysis demonstrated that both cell types expressed Pan-Cytokeratin, ZO-1, and E-cadherin proteins. Furthermore, immunoblotting analysis indicated significantly higher levels of hTERT and Ki67 proteins in iYNE (p < 0.001), and similar levels of Cluadin-3 and Occludin proteins (p ≥ 0.103).Proliferation curve analysis highlighted iYNE's serum-dependency and significantly enhanced proliferation capacities (p < 0.001). Additionally, pYNE and iYNE cells demonstrated comparable susceptibilities to infectious bovine rhinotracheitis virus (IBRV). These findings collectively suggest that the developed iYNE retains the evaluated physiological characteristics of pYNE, making it an appropriate in vitro model. This advancement will facilitate further investigation into the respiratory physiological and pathological mechanisms in yaks.